Navigating hepatotoxicity of antibody-drug conjugates: from mechanistic insights to clinical and postmarketing evidence - Dong, Yinuo; Zhi, Yang; Li, Xiaoyun; Ma, Mingyang; Ye, Minyan; Huang, Sha; Tang, Jieting; Zhong, Wei; Lei, Xiaohong; Mao, Yimin (Frontiers in Pharmacology, 2025)
Antibody-drug conjugates (ADCs) are rapidly developing targeted cancer therapeutic agents that combine specific monoclonal antibodies with cytotoxic agents. Currently, 17 ADCs are approved for the global market for treating hematological and solid tumors with more than 100 ADCs are in phase III clinical trials. ADC-induced hepatotoxicity is a significant concern with unclear mechanisms, and the incidence of hepatic adverse events (AEs) varies across different ADCs. Most hepatic AEs are moderate; however, some ADCs can cause life threatening or fatal AEs. The management of hepatic AEs is limited and is mainly based on product labeling information and the recommendations of study investigators. Therefore, it is critical to raise awareness among oncologists regarding ADC-related hepatotoxicity, and collaboration between oncologists and hepatologists is recommended to provide effective support. This review is the first to focus the hepatotoxicity of ADC, provide an overview of approved ADCs, summarize the potential mechanisms underlying hepatotoxicity, discuss the hepatic toxicities reported in clinical trials and postmarketing studies, and integrate the current recommended management strategies. This article will serve as a valuable resource for medical practitioners in comprehending and managing ADC-related hepatotoxicity, while facilitating further considerations regarding the clinical application of these novel agents.